Área de proteção ambiental estadual do rio Pandeiros, MG: espaço, território e atores - Bethonico, Maria Bárbara de Magalhães (2009)
The present society is marked by conflicts, including the crescent consumption and the environment preservation. In most specific situations the conflict reflects the socio-economic situation of small communities and seeks to survive in the extraction of natural resources. In areas of environmental protection such conflicts are translated, often in relationship involving local residents, government and companies, forming a game of power within a space. This research reflect on these conflicts, with the area of the APA Estadual do Rio Pandeiros and Refúgio Estadual de Vida Silvestre do Rio Pandeiros, with a focus on relations involving the production of charcoal and performance of the state as manager of the area. The understanding of these conflicts and their implications for communities and the management of land were the objectives of the research, considering the complexity of the relationship between the actors present there. The studies covered the ransom of geographical concepts and theories that the analysis based, in addition to the field of coal for identification, assessment of the environmental situation and application of interviews with leaders and people representing the communities, as well as officials of the IEF, as manager of the area. We identified three moments which marked the current configuration of the area, the first being defined not by the actions of the state, now called Sertão Mineiro . The second moment was the performance of the state in the implementation of economic policies with the reforestation of eucalyptus for the production of coal for the steel industry. The last moment was limited by the deployment of the unit of conservation APA Estadual do Rio Pandeiros , a fact that defined a new space organization, exacerbating the conflict. The survey results indicated that the conflicts are present, especially between the community and state, because the need for survival is the concern over environmental and preservation of the area, even considering some projects by sustainability, the effects of supervision and implementation of environmental fines. But such conflicts are not limited to that sphere, but is within the state itself which, pressured by the company and compliment with current legislation on the environment comes up against the need for demarcation of areas for protection. But the need to maintain the export of iron and other steel products makes the state will prioritize the production, a fact reflected in poor infrastructure offered to officials responsible for working with the communities and the lack of efficient public policies for economic development local, capable of inhibiting the action of coal, offering alternative for the residents.